2008
DOI: 10.1002/hed.20925
|View full text |Cite
|
Sign up to set email alerts
|

Wound‐healing modulation in upper airway stenosis—Myths and facts

Abstract: Wound healing plays a major role in the development of acquired subglottic stenosis. Pharmacologic treatment of subglottic stenosis must address both physiologic and pathologic healing processes. The relevant Pubmed and Ovid databases from 1960 to 2007 were systematically searched. Several modulating agents have been tested. Most of them were poorly investigated. Three modalities were thoroughly studied-steroids and antibiotics, mitomycin, and antireflux medications. However, there are conflicting data regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 153 publications
0
106
0
Order By: Relevance
“…The initial feasibility of the observer was investigated as a means to detect and classify surgically simulated edema in the subglottic airway of rabbits incorporating statistical decision theories. The ROC curve is an extremely useful tool that: (1) can measure image quality, (2) evaluate the performance of decision strategies, and (3) summarize the difficulty of such classification tasks. 13,14 Therefore, it is essential to first extract ROC curves from full-range OCT airway images in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial feasibility of the observer was investigated as a means to detect and classify surgically simulated edema in the subglottic airway of rabbits incorporating statistical decision theories. The ROC curve is an extremely useful tool that: (1) can measure image quality, (2) evaluate the performance of decision strategies, and (3) summarize the difficulty of such classification tasks. 13,14 Therefore, it is essential to first extract ROC curves from full-range OCT airway images in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This process in the subglottic region of airway may lead to stenosis, abnormal narrowing of airway. 1,2 As edema is the first physiologic event that occurs with injury, the early detection of edema in the subglottis may lead to improvement of airway management, early detection of tissue injury, and hence the prevention of stenosis. The gold standard for diagnosing subglottic edema in vivo is surgical endoscopy, but this is limited to the visual inspection of the airway surface or gentle palpation with blunt surgical instruments cantilevered off the surgeon's fingers.…”
Section: Introductionmentioning
confidence: 99%
“…The primary and most important complication of surgical treatments is recurrent stenosis related to formation of granulation tissue. 3 Some treatments are used to avoid the formation of granulation tissue and any one of the 3 stages of wound healing 5 : stage 1 (inflammation phase), antibiotics, corticosteroids, and hyperbaric oxygen therapy; stage 2 (proliferation phase), antibiotics, corticosteroids, mitomycin C, combination of 5-fluorouracil and triamcinolone Research was conducted for new treatment methods to prevent granulation formation in patients with tracheal stenosis. In a study conducted using estrogen and progesterone, Liman et al 6 showed that sex hormones prevent massive collagen and fibroblast proliferation in wound healing after tracheal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although it is not clear some results show that mitomycin C decreases fibroblast proliferation. Also, it is has been shown that mitomycin C slows wound healing during the inflammation and proliferation stages by decreasing basic fibroblast growth factor and TGF-␤1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of mitomycin C (MMC) is an emerging adjuvant therapy for BTS, and its efficacy has been evaluated in animal and clinical studies. In current studies, an amount of 0.4 mg/ml MMC is topically applied directly to the tracheal mucosa for 2-5min [4]; however, the efficacy and effective concentration of MMC in clinics is still under debate.…”
Section: Introductionmentioning
confidence: 99%